We were liars eaudiobook - Lockhart, E. (Listening Library, 2014)
#1 NEW YORK TIMES BESTSELLER • A modern, sophisticated suspense novel from National Book Award finalist, and Printz Award honoree E. Lockhart. Don't miss the #1 New York Times bestselling prequel, Family of Liars. A beautiful and distinguished family. A private island. A brilliant, damaged girl; a passionate, political boy. A group of four friends—the Liars—whose friendship turns destructive. A revolution. An accident. A secret. Lies upon lies. True love. The truth. Read it. And if anyone asks you how it ends, just LIE. "Thrilling, beautiful, and blisteringly smart, We Were Liars is utterly unforgettable." —John Green, #1 New York Times bestselling author of The Fault in Our Stars